PENGARUH KONSEP-DIRI DAN EFIKASI-DIRI TERHADAP DISIPLIN KERJA KARYAWAN BAGIAN PEMASARAN PT. PERTAMINA (PERSERO) UPMS V SURABAYA - Ronal Janti Exaudi Siregar (Universitas Indraprasta PGRI, 2016)
This study aimed to investigate the effect of self-concept and self-efficacy simultaneously against the disciplined employee. This study sample is 75 employees of sales at PT. Pertamina (Persero) UPMS V Surabaya. Data were collected through three scales, namely the scale of labor discipline, self-concept and self-efficacy. Test hypothesis with multiple regression analysis of obtained results that self-concept and self-efficacy simultaneously significant effect on employee discipline of sales at PT. Pertamina (Persero) UPMS Surabaya V (R ² = 0517; sign = 0.000) or p-value <0.05. This means that 51.7% of the variation in labor discipline variables can be explained by the variable self-concept and self-efficacy. While the remaining 48.3% is explained by other variables not examined, so it can not be explained.Keywords: Work Discipline, Self-Concept, Self-Efficacy.